Essentials of inorganic materials synthesis - Rao, C. N. R. (Chintamani Nagesa Ramachandra) 1934-; Biswas, Kanishka (John Wiley & Sons, Ltd., 2014)
This compact handbook describes all the important methods of synthesis employed today for synthesizing inorganic materials.